Grammatical Gender in Norwegian: Language Acquisition and Language Change. Issue 2 (28th May 2015) - Rodina, Yulia; Westergaard, Marit
Abstract : Based on data from two experimental studies, this paper investigates the production of gender in a Norwegian dialect (Tromsø) by several groups of child and adult speakers. The findings show that gender is late acquired (around age 7) and, furthermore, that there are considerable differences between the groups, indicating an ongoing historical change that involves the loss of feminine gender agreement. However, the feminine declensional endings, such as the suffixal definite article, are retained. While there are sociolinguistic factors causing this change, we argue that the nature of the change can be explained by the process of language acquisition. *